Teachers’ and Students’ Attitudes toward Shadow Education In Teaching and Learning English - Bhandari, Bhim Lal (Butwal Campus Journal, 2022)
This paper aims to explore teachers’ and students’ attitudes towards shadow education in teaching and learning the English language in the context of Nepal. This study adopts narrative inquiry as research method to explore the attitudes of participants through their lived narratives. For this purpose, two secondary-level English language teachers and two students have been selected as the participants who were involved in shadow education for the study from two community secondary schools in the Rupandehi district. The study uses unstructured interviews for collecting the required data. The study revealed that teachers and students have both positive and negative attitudes towards shadow education in English language teaching and learning. Tuition and coaching supported students to improve their self-confidence and language proficiency in English and teachers to be financially strong. Similarly, poor classroom teaching, attending fewer classes and giving less attention to the students during the regular teaching hours are the negative consequences of shadow education. Thus, the study can contribute to the discourse of shadow education to get insightful ideas and add new knowledge in reforming the existing educational policy in school education minimizing negative effects of it in Nepal.